Green Olive Browning Differ Between Cultivars - Goldental-Cohen, Shiri; Biton, Iris; Many, Yair; Ben-Sason, Sivan; Zemach, Hanita; Avidan, Benjamin; Ben-Ari, Giora (Frontiers in Plant Science, 2019)
CCurrently, table olives, unlike oil olives, are harvested manually. Shortage of manpower and increasing labor costs are the main incentives to mechanizing the harvesting of table olives. One of the major limiting factors in adopting mechanical harvest of table olives is the injury to fruit during mechanical harvest, which lowers the quality of the final product. In this study, we used the Israeli germplasm collection of olive cultivars at the Volcani Institute to screen the sensitivity of many olive cultivars to browning in response to injury. The browning process after induced mechanical injury was characterized in 106 olive cultivars. The proportional area of brown coloring after injury, compared to the total fruit surface area ranged from 0% to 83.61%. Fourteen cultivars were found to be resistant to browning and did not show any brown spot three hours after application of pressure. Among them, there are some cultivars that can serve as table olives. The different response to mechanical damage shown by the cultivars could be mainly due to genetic differences. Mesocarp cells in the fruits of the sensitive cultivars were damaged and missing the cell wall as a result of the applied pressure. The cuticles of resistant cultivars were thicker compared to those of susceptible cultivars. Finally, we showed that the browning process is enzymatic. We suggest cuticle thickness as an indicator of table olive cultivars suitable for mechanical harvest. A shift to browning resistant cultivars in place of the popular cultivars currently in use, will enable the mechanical harvest of table olive without affecting fruit quality.